Influence of soft clay on slope stability - Zakhir Firdaus B. Othman (School of Environmental Engineering, University Malaysia Perlis, 2014)
The purpose of this study was to investigate the effect of water absorption of soft clay on the reclaimed slope on it. The objective of this study was to analyze the soil strength when soaked in water to set a different time and to analyze slope stability on soft clay based on the infiltration of water from underground using Plaxis Software. In this study, soil samples were taken and tests were carried out on the land to get the unit weight, cohesion, and friction angle of the soil. Tests done to get the soil parameters are grain size analysis tests and unconfined compression test. Plaxis software is used to obtain a safety factor.